2010
DOI: 10.1007/s10549-010-0764-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among women recently diagnosed with invasive breast cancer: the Pathways Study

Abstract: Purpose-Few studies have assessed quality of life (QOL) of women diagnosed with breast cancer within the first few weeks of their initial diagnosis. We describe QOL among 950 women recently diagnosed with invasive breast cancer. Methods-Starting in January 2006, we invited women aged ≥21 years who were diagnosed with first primary invasive breast cancer within Kaiser Permanente Northern California (KPNC) to enroll in the Pathways Study, a prospective study of breast cancer survivorship. QOL was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
87
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 31 publications
21
87
9
Order By: Relevance
“…Park et al reported breast cancer survivors in Korea had higher scores in terms of physical well being, social well being, functional well being and breast cancer subscale. On the contrary, previous several studies suggested the older age patients are related to higher QOL (Mor et al, 1994;Ganz et al, 1998;Wenzel et al, 1999;Avis et al, 2005;Kwan et al, 2010). A study conducted in United State showed younger breast cancer patients are associated with problems with respect to partner relationships, sexual functioning, and body image, and less adaptive coping strategies, and the younger patients were more likely to have chemotherapy than older patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Park et al reported breast cancer survivors in Korea had higher scores in terms of physical well being, social well being, functional well being and breast cancer subscale. On the contrary, previous several studies suggested the older age patients are related to higher QOL (Mor et al, 1994;Ganz et al, 1998;Wenzel et al, 1999;Avis et al, 2005;Kwan et al, 2010). A study conducted in United State showed younger breast cancer patients are associated with problems with respect to partner relationships, sexual functioning, and body image, and less adaptive coping strategies, and the younger patients were more likely to have chemotherapy than older patients.…”
Section: Discussionmentioning
confidence: 94%
“…A study conducted in United State showed younger breast cancer patients are associated with problems with respect to partner relationships, sexual functioning, and body image, and less adaptive coping strategies, and the younger patients were more likely to have chemotherapy than older patients. Therefore, they were related to lower overall QOL than older breast cancer patients (Kwan et al, 2010). The inconsistency of these studies may be explained by differences in population background, source of subjects, sample size and by change.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, a meta analysis of breast cancer survivors from 16 studies found that those who got the recommended 150 minutes of exercise each week had an 11% reduction in breast cancer mortality, and a 24% lower risk of overall mortality [19]. In addition, remaining physically active during recovery from breast cancer can also help to improve quality of life, body image, mood, bone health, and physical condition, while at the same time reducing fatigue, stress, and anxiety [20][21][22][23][24][25][26]. In light of this and other findings, the American Cancer Society has made the following recommendations for breast cancer survivors to maintain their weight [27]:…”
Section: Physical Activity Recommendationsmentioning
confidence: 99%
“…Commonly used cancer-specific QoL measures, such as the Functional Assessment of Cancer Therapy-Breast (FACT-B; [7]) and the European Organization for Research and Treatment of Cancer (EORTC) Breast Cancer-Specific Quality of Life Questionnaire (QLQ-BR23; [8]), were designed primarily for cancer survivors in active treatment and have a predominance of items relevant to immediate effects of cancer diagnosis and treatment (e.g., nausea, shortness of breath). The impact of cancer on QoL during the acute diagnostic and treatment phases has been well studied [e.g., [9][10][11].…”
Section: Introductionmentioning
confidence: 99%